The effect of using the group learning strategy until mastery on the achievement of the female teachers’ institute students in history subject (Journal of the College of Basic Education, 2023)
Interest has increased in developing teaching methods and methods and using them to be more effective and productive than those traditional methods and methods in which the teacher is the center of activity in the educational and teaching process. Since what is required in the teaching position is that the student be the center of activity, and this is what modern educational trends seek to confirm.Field studies and experimental research revealed the existence of difficulties facing the teaching of history, and attributed this to several reasons, including the weakness of the knowledge of teachers of this subject in modern methods, and the weakness of their numbers in preparation that qualifies them to teach and their adoption of traditional methods in teaching.Despite the efforts that have been made in the field of developing methods and methods of teaching history, teaching is still restricted to old concepts, as we find that most of the teachers of this subject still focus on teaching based on memorization and indoctrination instead of focusing on activating the impact of the student and involving her in the teaching process.